Pospartum depressive symptoms: an associaiton with pregnancy planning and childbirth experience - Mohd Arifin, Siti Roshaidai (2012)
Background: Pregnancy and childbirth mark a critical episode of adjustment in a woman’s life and activate important developmental changes in the feminine identity. During these events, many biological, physiological, psychological, and relational factors are closely interrelating. Unfortunately, biological changes during pregnancy and childbirth may precipitate the development of depressive symptoms during postpartum period. Objective: To explore the association between postpartum depressive symptoms (PPDS) with pregnancy planning and childbirth experience in postpartum women at University Malaya Medical Centre (UMMC). Study Methods: A quantitative cross sectional survey using questionnaire has been conducted at two postnatal wards, UMMC to collect 347 postpartum women based on the inclusion and exclusion criteria. The data were analyzed using Pearson Chi square, Independent t-test and multiple logistic regression accordingly. Results: The prevalence of Postpartum Depressive Symptoms (PPDS) (Edinburgh Postpartum Depression Scale >12) was 31.7%. The finding revealed that women with unplanned pregnancy were more likely to have PPDS compared to women with planned pregnancy [45% (n = 45/100) vs. 26.3% (n =65/247); χ2 = 11.477, df = 1 p < 0.01]. Women with PPDS had a significantly lower score of Labour Agentry Scale [mean score=10.632, t=6.275, df=345, SD=1.694, CI 7.299-13.964, p < 0.0001]. The study clearly demonstrated that pregnancy planning and childbirth experience are predictors of PPDS. Conclusion: Psychological support for unplanned pregnancy and laboring women is crucial to prevent PPDS during postpartum period. Early detection of PPDS with a reliable instrument is the first key step to identify women at risk of postpartum depression.